Two new species of the genus Zaitzevia Champion, 1923 from China (Coleoptera: Elmidae: Macronychini) - Jiang, Ri-Xin; Wang, Shuo (Zootaxa, 2020)
Two new riffle beetles of the genus Zaitzevia Champion, 1923: Z. chenzhitengi sp. nov. from Sichuan Province and Z. xiongzichuni sp. nov. from Yunnan Province are described from China. Habitus and other diagnostic features of the new species are described and illustrated. Habitat information and collection data of the new species are also provided.